2018
DOI: 10.1155/2018/2782804
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Transcranial Direct Current Stimulation Reshapes Resting-State Brain Networks: A Magnetoencephalography Assessment

Abstract: Transcranial direct current stimulation (tDCS) can noninvasively induce brain plasticity, and it is potentially useful to treat patients affected by neurological conditions. However, little is known about tDCS effects on resting-state brain networks, which are largely involved in brain physiological functions and in diseases. In this randomized, sham-controlled, double-blind study on healthy subjects, we have assessed the effect of bilateral tDCS applied over the sensorimotor cortices on brain and network acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 73 publications
1
19
0
Order By: Relevance
“…However, tDCS‐cerebral cortex interaction is far more complex for at least the four following reasons. Firstly, in addition to the well‐known effect on cortical excitability, tDCS has an impact on several domains of brain function, including oscillatory activity, brain synchrony and hemodynamic processes (Herrmann, Rach, Neuling, & Strüber, ; Hoy, Bailey, Arnold, & Fitzgerald, ; Lang et al, ; Notturno, Marzetti, Pizzella, Uncini, & Zappasodi, ; Pellegrino et al, ; Stagg & Nitsche, ). Secondly, tDCS has remote effects in areas distant from the cortex underneath the stimulating electrodes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tDCS‐cerebral cortex interaction is far more complex for at least the four following reasons. Firstly, in addition to the well‐known effect on cortical excitability, tDCS has an impact on several domains of brain function, including oscillatory activity, brain synchrony and hemodynamic processes (Herrmann, Rach, Neuling, & Strüber, ; Hoy, Bailey, Arnold, & Fitzgerald, ; Lang et al, ; Notturno, Marzetti, Pizzella, Uncini, & Zappasodi, ; Pellegrino et al, ; Stagg & Nitsche, ). Secondly, tDCS has remote effects in areas distant from the cortex underneath the stimulating electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Remote effects have been attributed to interactions between the targeted brain area and connected areas forming a functional network (Fischer et al, 2017;Fox et al, 2014;Giambattistelli et al, 2014;Lindenberg, Nachtigall, Meinzer, Sieg, & Flöel, 2013;Peña-Gómez et al, 2012). tDCS-related remote effects have been demonstrated with a number of different read-outs of regional brain function, including BOLD signal (Polanía, Paulus, & Nitsche, 2012), measures of cortical excitability (Boros, Poreisz, Münchau, Paulus, & Nitsche, 2008;Lang, Nitsche, Paulus, Rothwell, & Lemon, 2004) and signatures of cortical activity and rhythms measured by electroencephalography and magnetoencephalography (Notturno et al, 2014;Pellegrino, Maran, et al, 2018). Thirdly, tDCS stimulation is a bipolar technique and its effects depend on the activity and position of both anode and cathode.…”
Section: Introductionmentioning
confidence: 99%
“…Speci cally, in our study the reduction of beta occurred for participants who already showed a higher level of beta power before the administration of Conventional tDCS. The inhibition of beta induced by anodal tDCS is not unusual in the literature 35,36 , despite previous evidence showing an opposite pattern, namely an increase of beta power 28 .…”
Section: Discussionmentioning
confidence: 63%
“…PLV owns a good time resolution and provides insight on the synchronization of fast changing electrophysiological dynamic. High PLV indicates higher synchronization (2327). We measured PLV for all possible channel combinations and averaged to obtain a measure of global connectivity.…”
Section: Methodsmentioning
confidence: 99%